Clergy attitudes toward vaccines and vaccine advocacy: a qualitative study. Issue 11 (1st November 2020) - Williams, Joshua T. B.; Fisher, Michael P.; Bayliss, Elizabeth A.; Morris, Megan A.; O'Leary, Sean T.
ABSTRACT: Background : Recent outbreaks of vaccine-preventable diseases have affected members of religious communities. While major religions support vaccines, the views of individual clergy who practice and propagate major faith traditions are unclear. Our objective was to explore clergy attitudes toward vaccines and vaccine advocacy. Methods : In 2018–2019, we conducted qualitative interviews with clergy in Colorado and North Carolina. We inductively analyzed transcripts using a grounded theory approach, developing codes iteratively, resolving disagreements by consensus, and identifying themes. Results : We interviewed 16 clergy (1 Buddhist, 3 Catholic, 2 Jewish, 1 Hindu, 1 Islamic, 7 Protestant, and 1 Unity). Analyses yielded seven themes: attitudes toward vaccines, congregational needs, public health climate, perceived responsibility, comfort and competing interests, reported advocacy efforts, and clergy health advocacy goals. Most clergy had positive vaccination attitudes and were open to vaccine advocacy, although discomfort with medical concepts and competing interests in their congregations influenced whether many had chosen to advocate for vaccines. Over half reported promoting vaccination in various contexts. Conclusions : In our sample, U.S. clergy held complex attitudes toward vaccines, informed by experience and social norms as much as religious beliefs or Scriptures. Clergy may be open to vaccine advocacy, but a perceived lack of relevance in their faith communities or a lack of medical expertise may limit their advocacy efforts in diverse contexts. Amidst growing vaccine hesitancy, pediatricians could partner with clergy in their communities, answer questions about vaccines, raise awareness of recent outbreaks, and empower clergy in joint educational events.